The Effect of Current Ratio, Debt to Equity Ratio, and Return on Assets on Financial Distress - Amin Hou; Sabaruddin Chaniago; Sri Kawuri; Tyus Windi Ayuni; Dwi Pertiwi Anggraini (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The banking sector is a key driver of economic growth and financial stability, but it remains exposed to various risks that can lead to financial distress. Early detection using financial ratio analysis is therefore essential to strengthen resilience and protect stakeholder confidence. This study aims to examine the impact of financial ratios on financial distress. This study analyzes the current ratio, debt to equity ratio, and return on assets. The employed study methodology is a quantitative technique utilizing secondary data obtained from financial reports. Data were evaluated by multiple linear regression to ascertain both partial and simultaneous impacts of financial ratios on financial hardship. The findings indicate that current ratio, debt equity ratio, and return on assets significantly influence financial strain to some extent. Concurrent testing indicates that the three independent factors collectively exert a significant impact on financial hardship, with a determination coefficient of 75.9%. These findings affirm that effective management of liquidity, debt composition, and profitability is essential in mitigating the risk of financial distress within the banking industry. Practically, banks should actively manage liquidity, debt, and profitability to prevent financial distress.